2011
DOI: 10.11336/jjcrs.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the intensity of stroke rehabilitation and outcome: A survey conducted by the Kaifukuki Rehabilitation Ward Association in Japan (second report)

Abstract: were signifi cantly lower in the ≥6 units group than in the other 2 groups. The number of days spent in the rehabilitation facility was signifi cantly lower, by approximately 12 days, in the ≥6 units group than in the other groups. Conclusion: These results revealed that facilities providing ≥6 units/day of rehabilitation even on holidays enabled patients to be discharged from the facility in signifi cantly fewer days, despite accepting patients with more severe stroke, compared to facilities providing fewer u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Next, though there should be differences in the number of rehabilitation units, the relationship between rehabilitation time and patient severity has not been clear. Although a positive relationship between rehabilitation time and patient outcomes has been reported in the post-acute stage [ 31 , 32 ], there is no consensus about the acute stage [ 33 ]. Some studies report that, by increasing intensity of rehabilitation in the acute stage, post-stroke severity in patients would be improved [ 3 , 4 ]; however, Lauro et al reported no significant effect of the same [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, though there should be differences in the number of rehabilitation units, the relationship between rehabilitation time and patient severity has not been clear. Although a positive relationship between rehabilitation time and patient outcomes has been reported in the post-acute stage [ 31 , 32 ], there is no consensus about the acute stage [ 33 ]. Some studies report that, by increasing intensity of rehabilitation in the acute stage, post-stroke severity in patients would be improved [ 3 , 4 ]; however, Lauro et al reported no significant effect of the same [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the motor FIM score gain, the motor FIM effi ciency, and the rate of discharge to home were signifi cantly higher in the group with seven to nine units of rehabilitation than in the group with fi ve to six units of rehabilitation. Nagai et al [22] compared the amount of exercise and the rehabilitation outcomes among many hospitals. Classifying 11 hospitals into three groups according to the number of rehabilitating units offered: less than four units, four or fi ve units, and six or more units, they reported that the motor FIM effi ciency was signifi cantly higher in the hospitals offering six or more units than in those offering less than four units.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are diffi culties in clarifying the relationship between the amount of exercise and rehabilitation outcomes. A previous study reported that the rehabilitation systemrelated factors that affected the rehabilitation outcomes in a hospital included the number of staff members, the layout of the hospital ward, the equipment and instruments of the hospital, and cooperation with other medical and welfare institutions [22]. Considering the fact that not only the amount but also the quality of rehabilitation affects the rehabilitation outcomes, it is understandable that there was a signifi cant difference in FIM score gain between the two groups classifi ed according to the amount of exercise in the report of Jeong et al [19] and that the ranking of the three hospitals based on adjusted FIM effi ciency differed from that based on the amount of exercise in our study.…”
Section: Discussionmentioning
confidence: 99%